2011
DOI: 10.3892/or.2011.1551
|View full text |Cite
|
Sign up to set email alerts
|

Denbinobin, a phenanthrene from dendrobium nobile, inhibits invasion and induces apoptosis in SNU-484 human gastric cancer cells

Abstract: Abstract. Dendrobium nobile is widely used as an analgesic, an antipyretic, and a tonic to nourish the stomach in traditional medicine. Mounting evidence suggests an antitumor activity of denbinobin, a major phenanthrene isolated from stems of Dendrobium nobile. The present study aimed to investigate the inhibitory effect of denbinobin on the invasive ability of human cancer cells. The cytotoxicity of denbonobin was examined in several human cancer cell lines including SK-Hep-1 hepatocarcinoma cells, SNU-484 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…It significantly decreased the expressions of matrix metalloproteinase (MMP-2) and (MMP-9) and induced apoptosis through downregulation of Bcl-2 and upregulation of Bax in cancer cells. These findings may be used to provide reference for further studies on the pharmacological mechanisms from denbinobin and polysaccharides in D. nobile [ 50 , 51 , 84 ].…”
Section: The Pharmacological Effects Of Dendrobium mentioning
confidence: 99%
“…It significantly decreased the expressions of matrix metalloproteinase (MMP-2) and (MMP-9) and induced apoptosis through downregulation of Bcl-2 and upregulation of Bax in cancer cells. These findings may be used to provide reference for further studies on the pharmacological mechanisms from denbinobin and polysaccharides in D. nobile [ 50 , 51 , 84 ].…”
Section: The Pharmacological Effects Of Dendrobium mentioning
confidence: 99%
“…Furthermore, CCl 4 -induced hepatic injury has been extensively used in animal models to evaluate the therapeutic potential of drugs. On the other hand, plants of the Dendrobium genus ( Orchidaceae ) are used in traditional herbal medicines in Asia, and studies have shown that they contain a wide variety of medicinal properties [ 11 13 ]. Moniliformediquinone (2,6-dimethoxy-1,4,5,8-phenanthradiquinone; MFD) (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In ancient Chinese medical literature dating back over a thousand years, Dendrobium extracts were reported to improve vision [11]; however, there is still no firm understanding of the chemical components and mechanism of these extracts on vision. Recent research indicates that Dendrobium extracts may also have other bioactive properties, including the induction of apoptosis in human gastric cancer cells [12], the facilitation of neuroprotection against stress-induced apoptosis in PC12 cells [13], the inhibition of lipopolysaccharide- (LPS-) induced memory impairment in rats [14], and the LPS-induced nitric oxide production in macrophages [15]. It has also been suggested that Dendrobium extracts have strong antioxidant properties in vitro [16].…”
Section: Introductionmentioning
confidence: 99%